Biopolymer starch mediated synthetic route of multi-spheres and donut ZnO structures. (22nd January 2015) - Carp, Oana; AlinaTirsoaga,; Jurca, Bogdan; Ene, Ramona; Somacescu, Simona; Ianculescu, Adelina
Highlights: Biopolymer starch as phase and morphology controller in ZnO synthesis. A synthesis method of multi-spheres ZnO–starch composite was developed. Thermal processing facilitates the formation of donut-like ZnO morphology. The ZnO based structures prove motivating optical and photocatalytical properties. Abstract: A starch-assisted synthetic methodology of multispheres ZnO–starch biocomposites was developed. An additional thermal processing of the ZnO–starch composites induces the formation of ZnO with donut-like morphology. The synthesis of single-phase zinc oxide with a spherical morphology is conditioned by the presence of starch, which acts as template, stabilizing/capping agent. The synthesized structures present significant photocatalytic activities; a total phenol mineralization is attained with the donut-like ZnO photocatalyst under visible light irradiation, due to a cumulative effect of the its relatively large specific surface area, high crystallinity and favorable combination of defects for band narrowing, which together permit an enhanced utilization rate of the light.